AN AUTISTIC STUDENT’S LANGUAGE LEARNING STRATEGIES IN WRITING POEM - Aulia Maulidiyah; Nani Ronsani Thamrin; Erwin Oktoma (Journey: Journal of English Language and Pedagogy, 2023)
This research sought to investigate the contribution of language learning strategies in the poem writing of an autistic student attending a special need school in Kuningan. This study used qualitative case, case study methods to analyze the cases in detail. To assess the data’s naturalness, observations and interviews were used to gather the data. And to investigate the difficulties faced by autistic students writing poems. The research was done at a special school in Kuningan and included one student with autism among seven other students. Results indicated that autistic students utilized motivation in social-emotional strategies. It was also noted that students with autism found vocabulary, tenses, and rhymes to be a challenge in writing poems. But she also learned how to overcome vocabulary by using cognitive translation strategies to acquire new vocabulary she didn't know, and using tenses by asking questions about it using social-emotional clarification strategies